Nitrate is an important nitrogen source for Arctic tundra plants - Liu, Xue-Yan; Koba, Keisuke; Koyama, Lina A; Hobbie, Sarah E; Weiss, Marissa S; Inagaki, Yoshiyuki; Shaver, Gaius R; Giblin, Anne E; Hobara, Satoru; Nadelhoffer, Knute J; Sommerkorn, Martin; Rastetter, Edward B; et al. (Proceedings of the National Academy of Sciences - PNAS, 2018)
Plant nitrogen (N) use is a key component of the N cycle in terrestrial ecosystems. The supply of N to plants affects community species composition and ecosystem processes such as photosynthesis and carbon (C) accumulation. However, the availabilities and relative importance of different N forms to plants are not well understood. While nitrate (NO ) is a major N form used by plants worldwide, it is discounted as a N source for Arctic tundra plants because of extremely low NO concentrations in Arctic tundra soils, undetectable soil nitrification, and plant-tissue NO that is typically below detection limits. Here we reexamine NO use by tundra plants using a sensitive denitrifier method to analyze plant-tissue NO Soil-derived NO was detected in tundra plant tissues, and tundra plants took up soil NO at comparable rates to plants from relatively NO -rich ecosystems in other biomes. Nitrate assimilation determined by N enrichments of leaf NO relative to soil NO accounted for 4 to 52% (as estimated by a Bayesian isotope-mixing model) of species-specific total leaf N of Alaskan tundra plants. Our finding that in situ soil NO availability for tundra plants is high has important implications for Arctic ecosystems, not only in determining species compositions, but also in determining the loss of N from soils via leaching and denitrification. Plant N uptake and soil N losses can strongly influence C uptake and accumulation in tundra soils. Accordingly, this evidence of NO availability in tundra soils is crucial for predicting C storage in tundra.